Smart Control Monitors the Active Period of Using Biofilters on Motor Vehicle Exhausts: Smart Control Monitors the Active Period of Using Biofilters on Motor Vehicle Exhausts - Agus Darwanto; Edi Mustofa Yulianto; Nafisah Nurhayati (Jurnal E-Komtek, 2022)
Many natural ingredients can be used as biofilters, but the use of biofilters is constrained by the difficulty of knowing when the saturation period is so that the active ingredients can be replaced immediately. The research aims to make a smart control of the active period of a motor vehicle exhaust biofilter that effectively provides information about the active period of the biofilter used. The tools and materials used are motorbikes, exhaust biofilters, MQ-135 sensors, exhaust filter housings, ESP8266 Node MCUs, 16 x 2 LCDs, switches, jumper cables and smartphones. The data collection method uses measuring CO2 levels using the MQ-135 sensor, which is read on the LCD screen and sends notifications to smartphones via the Telegram application. Data analysis used descriptive statistical analysis presented in tables and graphs. The results showed that the smart control filter is a blend of leaf biofilter Simplicia, filter housing, MQ-135 sensor, power bank, IoT, LCD screen and cellphone installed with the Telegram application. To turn on the sensor so it can send notifications to the LCD screen mounted on the speedometer, you need to turn on the ON button. CO2 levels and filter status will be read on the LCD screen. Notifications are also sent to cellphones via the telegram application so owners can find CO2 levels and control the active period of using leaf biofilter simplicial.